The association between organochlorine and thyroid hormone levels in cord serum: A study from northern Thailand - R. Asawasinsopon (2018)
It is now known that many organochlorines (OCs) act as endocrine disruptors, causing harmful effects on wildlife and humans. Several field and laboratory animal studies have reported that OCs cause adverse effects on thyroid hormone status. However, data regarding their effects on thyroid hormone status in humans are inconclusive. Because a developing fetus is especially sensitive to hormonal disruption by exposure to OCs, the adverse health effects on infants are of concern. The present study aimed to investigate the association between OC levels in maternal and cord serum, and the association between OC and thyroid hormone levels in cord serum. The study was performed with 39 mother-infant pairs from Mae Rim District of Chiang Mai Province, northern Thailand, who had normal delivery and full term gestation. Maternal blood was collected for measuring OCs and total lipids. Umbilical cord blood was collected for measuring OCs, total lipids, and thyroid hormones, including total thyroxine (TT4), free thyroxine (FT4), and thyroid stimulating hormone (TSH). 1,1-dichloro-2,2-di(4-chlorophenyl)ethylene (p,p′-DDE) had the highest level in all serum samples with a geometric mean of 1191 ng/g lipids in maternal serum and 742 ng/g lipids in cord serum. The second highest level was that for 1,1,1-trichloro-2,2-di(4-chlorophenyl)ethane (p,p′-DDT), followed by 1,1-dichloro-2,2-di(4-chlorophenyl)ethane (p,p′-DDD). Levels of p,p′-DDE, p,p′-DDT, p,p′-DDD, and dieldrin in maternal serum were positively associated with levels in cord serum (r = 0.86, 0.77, 0.66, and 0.60, respectively; P < 0.001). The important findings were that cord serum TT4levels were negatively associated with cord serum levels of p,p′-DDE (r = - 0.37, P = 0.024), p,p′-DDT.3 (r = - 0.33, P = 0.048), and 1,1-dichloro-2-(2-chlorophenyl)-2-(4-chlorophenyl)ethylene (o,p′-DDE) (r = - 0.76, P = 0.019). These results therefore suggest that exposure to DDT and its metabolites during fetal development may cause some effects on thyroid hormonal status in infants. © 2006 Elsevier Ltd. All rights reserved.